Izin Pernikahan Poligami Di Kecamatan Playen - Muthmainnah, Muthmainnah; Al Amin, M. Nur Kholis; Syaifuddin, Endang; Asmorohadi, Asmorohadi (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2022)
This research aims to explore the reasons for candidates and judges' considerations in permitting polygamous marriages at the KUA, Playen District, Gunungkidul Regency in 2012-2015. In this rural area, polygamous marriages are quite large. Sociological juridical research is carried out with a qualitative approach. Information collection was carried out by searching polygamy decision documents in the KUA of Playen District in 2012-2015 accompanied by interviews with KUA officials at the research location. Based on the content analysis, it has been found that there are two types of reasons considered by the judges in determining the permit for polygamous marriages. Suggestions for tightening administrative requirements and the intensity of socialization of polygamous marriages can be carried out by KUA so that marriage registration can run well without harming all parties.